Commodification of Content in the Soap Opera “Si Doel Anak Sekolahan” - Farah Laila Fazriah; Sigit Surahman; Yudhistira Ardi Poetra (LONTAR: Jurnal Ilmu Komunikasi, 2023)
Commodification is the process of transforming use value into exchange value. The soap opera Si Doel Anak Sekolahan is the result of efforts to change from a use value that can entertain into an exchange value that brings financial benefits. These shows attract a large audience, which attractive to advertisers in various ways. This show is repeated every year from 2011 to 2023. This research uses a critical perspective by looking at the political economy of media. The concept of content commodification offered by Vincent Mosco became the scalpel for this research. Data for this study comes from the main source, namely the soap opera "Si Doel Anak Sekolahan" on RCTI. Meanwhile, additional data such as observations and documentation were obtained from literature studies, literature and internet searches. The results of research show that the soap opera drama series Si Doel Anak Sekolahan contains content commodification in the form of advertisements in the form of billboards, there are also advertisements in the form of squeeze frames. Media institutions have the power determine what programs will be made into new commodities on the television. Every program produced by media institution is a marriage between the economic system and the political system.